2023
DOI: 10.3390/app13095681
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Degradation of Pharmaceutical Trimethoprim in Aqueous Solution over Nanostructured TiO2 Film Irradiated with Simulated Solar Radiation

Abstract: Pharmaceuticals are characterized by a wide range of physical, chemical, and biological properties and functionalities that contribute to their inherent complexity as compounds. Unfortunately, human carelessness during the production, use, and disposal of these compounds results in their presence in the environment. This study utilized a nanostructured TiO2 film on a glass ring at the bottom of a reactor and simulated a solar radiation lamp as the radiation source for both photocatalytic and photolytic experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…It is known that a platy structure is the most common morphology for nanolayered structures, which are produced by building LDHs [1][2][3]. Scanning electron microscopy produced the images of the Ni-Zn-Ti LDH shown in Figure S1.…”
Section: Characterizations Of the Ni-ti-zn Nanolayers And Ni-ti-zn-or...mentioning
confidence: 99%
See 2 more Smart Citations
“…It is known that a platy structure is the most common morphology for nanolayered structures, which are produced by building LDHs [1][2][3]. Scanning electron microscopy produced the images of the Ni-Zn-Ti LDH shown in Figure S1.…”
Section: Characterizations Of the Ni-ti-zn Nanolayers And Ni-ti-zn-or...mentioning
confidence: 99%
“…Photocatalytic processes are a kind of benign light-based technique whereby light is used as an energy source to excite photoactive materials and produce strong oxidizing agents that convert the organic pollutants to CO 2 and water. Previous studies of photocatalytic processes [1][2][3] concluded that the structure of the photocatalysts plays an important role in increasing their photo-related activities and the efficiency of the photocatalytic processes. Saber et al [1,2] designed novel nanohybrids based on inorganicmagnetic-organic structures for increasing the performance of photocatalysts to remove dyes from water.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the unique surface properties of TiO 2 nanoparticles, including their expansive surface area and the presence of surface defects, play a pivotal role in augmenting the efficiency of the photodegradation process. These attributes facilitate the adsorption of organic contaminants onto the nanoparticle surface, thereby enhancing the probability of interaction with photoexcited charge carriers and fostering degradation reactions [25,26].…”
Section: Photocatalytic Degradation Of Am Mo and Qymentioning
confidence: 99%